Islam as political religion : the future of an imperial faith - Akhtar, Shabbir (Routledge, 2011)
This comprehensive survey of contemporary Islam provides a philosophical and theological approach to the issues faced by Muslims and the question of global secularisation. Engaging with critics of modern Islam, Shabbir Akhtar sets out an agenda of what his religion is and could be as a political entity.